O Bałtyku, polskiej wsi oraz edukacji na dwa głosy: Stanisław Pigoń i Bernard Chrzanowski - Nowicka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article constitutes a commentary on the “common spaces” in the writings of Stanisław Pigoń and Bernard Chrzanowski (Chrzanowski: a social and education activist living in Greater Poland at the turn of the 20th century). They represented different generations and came from different social environments. Pigoń and Chrzanowski most likely met during Pigoń’s stay in Poznań; before that, they knew each other’s texts, which expressed similar conviction on the significance of the Baltic Sea for Polish culture and the future Polish state. Since the regaining of independence, they devoted significant attention to the rural areas and the education of their inhabitants. The tasks they set in this area for the intelligentsia can be placed on the axis of the so-called “intelligentsia’s revision literature” which spanned a few generations in Poland.